Married 'Urfi in the View of Contemporary Scholars Sheikh Muhammad Ali Jum'ah - Rozali, M; Hikmah, Ulya; Yuliatin, Yuliatin (Universitas Islam Negeri Raden Intan Lampung, 2023)
While marriage is an Islamic law and essentially a necessity, there are contradictions between the term and the application of marriage in society. One of them is nikah 'urfi, which is seen as invalid based on the rules of a country but is valid in the view of sharia. This article aims to reveal Muhammad 'Ali Jum'ah's thoughts on nikah 'urfi, furthermore the relevance of nikah 'urfi in the modern era. This article uses a descriptive qualitative approach and literature type by examining writings to solve a problem in a critical and in-depth manner. The approach in this article is to examine the thoughts of Muhammad 'Ali Jum'ah. The results of writing the article found that nikah'urfi is a marriage that fulfills all the pillars and conditions, but is not recorded at the marriage registration institution. Nikah 'urfi is a marriage with complete terms and conditions, this marriage is valid and has been legalized by the Fatwa Institute of Dār al-Ifta' Egypt, through the Fatwa of Mufti Diyar of the Arab Republic of Egypt Muhammad 'Ali Jum'ah. This fatwa was issued due to the prevalence of 'urfi marriage and the high cost of marriage. Contemporary scholars differ in opinion, with some legalizing and others forbidding it in light of current conditions. Keyword: 'Urfi Marriage, The Thought of Muhammad 'Ali Jum'ah